Cybersecurity and Incident Response Challenges in the African Continent: a Case of the Nigerian System - (:unkn) unknown (My University, 2023)
This conference paper focuses on the cybersecurity and incident response challenges faced by theAfrican continent, specifically in the case of the Nigerian system. The study aims to identify the majorcybersecurity threats and challenges faced by the Nigerian system and evaluate the current incidentresponse strategies in place. The paper provides a comprehensive overview of the cybersecuritylandscape in Nigeria, including the current state of cybersecurity infrastructure, legislativeframeworks, and the role of various stakeholders in ensuring the security of critical nationalinfrastructure. Additionally, the paper presents a case study of a major cybersecurity incident inNigeria, highlighting the challenges faced in responding to the incident and the lessons learned. Thepaper concludes by recommending strategies for improving incident response capabilities in theNigerian system and the African continent as a whole, with the goal of strengthening cybersecurityand ensuring the protection of critical national assets.
Keywords: African Research